Correlation between physical properties of superlattices obtained by means of electrochemical deposition method and ion spraying - Duś-Sitek, Marta; Nabiałek, Marcin; Gągorowska, Barbara (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
This paper compares structural and magnetic properties of Cu/Ni and Ni/Cu multilayer systems obtained by means of ion sputtering and electrochemical deposition method. The impact of both thickness of Cu and Ni sublayers and a number of bilayers repetition on magnetic properties was also investigated. The purpose of this work was to verify which method for multilayer system deposition enables samples of better structural and magnetic properties to be obtained.
Optica Applicata, Vol. 39, 2009, nr 4, s. 645-653
Keywords: optyka; multilayer systems; superlattice; ion sputtering; electrochemical deposition